A robust photoswitchable dual-color fluorescent poly (vinyl alcohol) composite hydrogel constructed by photo-responsive FRET effect. (December 2022) - Zhang, Xin; Wang, Beibei; Zheng, Zhiyu; Yang, Guiqiang; Zhang, Chao; Liao, Liqiong
Abstract: Stimuli responsive fluorescence characteristics are significant in some fields, such as sensors, information encryption, and bionic camouflage. In this work, a robust poly(vinyl alcohol) (PVA) hydrogel with photoswitchable dynamic fluorescence behaviors was constructed by incorporating dual-color fluorescent nanoparticles (DCFNs). The DCFNs were composed of the spiropyran-modified β-cyclodextrin (β-CD-SP) and nitrobenzoxadiazolyl (NBD) derivatives, which could exist in the PVA network through non-covalent interaction. The SP moiety functioned as an acceptor and realized the photoisomerization to further quench or recover the fluorescence of the NBD moiety based on the fluorescence resonance energy transfer (FRET) effect. Therefore, under the irradiation of ultraviolet light (UV) or visible light (Vis), the hydrogel showed a fluorescence emission peak of merocyanine (MC) at 660 nm (red) or NBD at 550 nm (green), respectively. Additionally, the pH responsive characteristic of the MC chromophore also endowed the hydrogel with pH responsive fluorescence behaviors. Utilizing these advantages, specific patterns can be displayed on the hydrogel in dual mode through a hollowed-out photomask. The hydrogel could also be utilized as dual-color "building blocks" to construct various 2D or 3D structures. This composite hydrogel has potential application in various fields, such as sensors, optical switch, information storage, and biomimetic components. Graphical abstract: Image 1 Highlights: DCFNs are successfully introduced into the hydrogel via the non-covalent interaction. The non-covalent bond endowed the hydrogel with desired mechanical properties. The hydrogel could emit dual-color fluorescence based on FRET effect.